Pengaruh Perkembangan Pendidikan Karakter Dalam Mengatasi Masalah Bullying Di Indonesia - Aprilia Yola Azhari; Dwi Lutfiana Nur Janah; Fadhila Eka Meyliana; Bagus Setiawan (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
Indonesia is a country that upholds the implementation of quality education to support the progress of the Indonesian State through its Human Resources. Education is not only obtained from school, but education can also be obtained in the environment where a person lives and socializes. However, education in Indonesia is also not free from various problems, one of which is the emergence of bullying that occurs in the school environment. There are many factors that result in bullying, and this behavior is deviant and not in accordance with applicable norms. The existence of bullying behavior causes the need for character cultivation through character education which must be instilled in children as early as possible. Character education is considered to have an important role and can be one solution to guide children so that they have the ability to differentiate between good and bad actions as well as actions that are pleasing and detrimental to other people. Character education must not only be carried out and implemented at school, but it must also be implemented and supervised directly by parents. By cultivating this character, it is hoped that the quality of education in Indonesia will increase.